2017
DOI: 10.1073/pnas.1617251114
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing virtual reality for all users through gaze-contingent and adaptive focus displays

Abstract: From the desktop to the laptop to the mobile device, personal computing platforms evolve over time. Moving forward, wearable computing is widely expected to be integral to consumer electronics and beyond. The primary interface between a wearable computer and a user is often a near-eye display. However, current generation near-eye displays suffer from multiple limitations: they are unable to provide fully natural visual cues and comfortable viewing experiences for all users. At their core, many of the issues wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(89 citation statements)
references
References 37 publications
0
88
0
1
Order By: Relevance
“…We ran set of user studies collecting data from a total of 173 people. The studies evaluate whether an adaptive focus mode (below) can adequately address the VAC, using both objective autorefractor measurements of accommodation, and subjective preferences [5]. In addition, we also consider the effects of age (for presbyopia) and refractive errors on these metrics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We ran set of user studies collecting data from a total of 173 people. The studies evaluate whether an adaptive focus mode (below) can adequately address the VAC, using both objective autorefractor measurements of accommodation, and subjective preferences [5]. In addition, we also consider the effects of age (for presbyopia) and refractive errors on these metrics.…”
Section: Methodsmentioning
confidence: 99%
“…A translation stage adjusts inter-eye separation and near-infrared (NIR) / visible light beam splitters allow for simultaneous stimulus presentation and accommodation measurement. Figure adapted from[5].…”
mentioning
confidence: 99%
“…Padmanaban et al [25] used a display with refocusable lenses to investigate the impact of refocusable graphics on users to go even further and personalize the accommodation to each individual to correct vision impairments.…”
Section: Impact Of Dof Renderingmentioning
confidence: 99%
“…Nevertheless, conventional stereoscopic and auto-stereoscopic displays are known to cause visual fatigue owing to the vergence-accommodation conflict (VAC) [1], which limits long-time observation and its usage for children. Numerous types of displays have been proposed to correct VAC in autostereoscopic displays, including holographic [2], super multiview [3], and light field [4] displays, while recently a rapid increase in head-mounted displays research has been observed [5][6][7][8]. This study proposes 3D glasses for stereoscopic displays that solve the problem of VAC so that high-resolution 3D images can be viewed with reduced visual fatigue.…”
Section: Introductionmentioning
confidence: 99%